The Relationship Between Leg Muscle Strength and The Ability of The Pencak Silat Sickle Kick - Firdaus, Kurniawan; Jufrianis, Jufrianis (Universitas Negeri Padang, 2024)
Background and Aim. physical components such as leg muscle strength play an important role in determining the effectiveness of kicking techniques, particularly the sickle kick. However, the relationship between physical strength indicators and kicking ability is still not fully understood. Therefore, this study aims to determine the relationship between leg muscle strength and the ability to perform sickle kicks among Muhammadiyah Bangkinang Middle School students.Methods. This study uses a multiple correlation research design. The population consisted of 22 students, and the sampling technique employed was total sampling. Data were collected through observation, literature study, and test or measurement techniques. Data analysis was conducted using correlation tests to examine the relationship between variables with interval or ratio data.Results. The results indicate a significant relationship in the opposite direction between vertical jump performance and sickle kick ability, with a correlation coefficient of 0.579. The significance value (Sig. 2-tailed) is smaller than α = 0.001 (0.000 < 0.001), with a contribution percentage of 80%.Conclusion. There is a significant and inverse relationship between vertical jump performance and sickle kick ability among Muhammadiyah Bangkinang Middle School students.